2016
DOI: 10.1080/0284186x.2016.1175658
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of non-participation in a mass screening program for colorectal cancer in Finland

Abstract: Background: For an effective colorectal cancer (CRC) screening program, high participation rate is essential. However, non-participation in CRC screening program has increased in Finland. Material and methods: The study was based on a population-based nationwide cohort of persons invited for CRC screening in [2004][2005][2006][2007][2008][2009][2010][2011]. Information on the first round of the CRC screening participation and related background factors was obtained from the Finnish Cancer Registry, and informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…In Flanders, males, younger age groups, lower socio-economic groups and immigrants (except Dutch) are less likely to participate in the CRC screening programme. These findings are in line with other European countries [18,25]. The CRC screening by FIT is completely free of charge, indicating that other than financial factors play a role.…”
Section: Discussionsupporting
confidence: 89%
“…In Flanders, males, younger age groups, lower socio-economic groups and immigrants (except Dutch) are less likely to participate in the CRC screening programme. These findings are in line with other European countries [18,25]. The CRC screening by FIT is completely free of charge, indicating that other than financial factors play a role.…”
Section: Discussionsupporting
confidence: 89%
“…This is in contrast to other health behavioral and preventative care intervention studies in the literature, which historically suggest a higher rate of non-participation and drop-out among smokers [20, 21, 25, 26]. In this case, we would have expected to see a higher decline rate compared to consent rate in the intervention sites.…”
Section: Discussioncontrasting
confidence: 63%
“…Our findings for the influence of health behaviours on CRC screening participation add to the limited evidence available. Studies based on CRC screening programmes in England, Finland and France, [13][14][15] as well as studies of CRC screening in the United States 16 17 have found similar associations between current smoking and non-participation in CRC screening. Our study did not find significant…”
Section: Discussionmentioning
confidence: 85%